Preliminary findings on the volatile oil obtained from the fresh leaves of Citron Citrus medica L. (Fam. Rutaceae) - Lubuguin, Antonina Tela
The fresh leaves of Citrus medica L. (Family Rutaceae) common name citron yielded 0.3% v/w of citron oil and a moisture content of 74.5%.